Western Drywood Termite, Incisitermes minor (Hagen) (Insecta: Isoptera: Kalotermitidae) - Brian J. Cabrera; Rudolf H. Scheffrahn (EDIS)
The western drywood termite, Incisitermes minor (Hagen), is the most common structure-infesting drywood termite in the southwestern United States. Originally described as Kalotermes minor by Hagen (1858), I. minor was reclassified into the genus Incisitermes by Krishna (1961). In California, Incisitermes minor infestations are still sometimes referred to by some pest control operators as "Kalos" and designated with a "K" on termite inspection reports. Currently, there is only one Kalotermes species in the United States (Kalotermes approximatus (Snyder), found in Florida and the southeastern U.S. north to Virginia). Some members of the Kalotermitidae are called drywood termites because colonies live entirely within sound, dead, dry wood. Drywood termites do not require any contact with the ground. This document is EENY-248, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001. Revised: December 2005.